Experimental validity on the casting characteristics of stir cast aluminium composites - Gowrishankar M C; Pavan Hiremath; Manjunath Shettar; Sathyashankara Sharma; Satish Rao U (Journal of Materials Research and Technology, 2020)
In the present work efforts are made to confirm the presence of actual weight percentage of reinforcements and its effect on aluminium alloy composites during stir casting technique. Two types of reinforcements, such as Silicon carbide and Boron carbide, were used by varying weight to manufacture Al6061 composites. The manufactured composites after stir casting show uniform distribution of hardness on the entire cross-section measured from top to bottom. The dissolved composites during the acid solubility test show approximately 95% of reinforcements present in the aluminium composites. Presence of reinforcements and quantity play a very important role to augment the properties of aluminium alloy by altering the microstructure during solidification and induces strain energy in the metallic matrix alloy. Almost 50–80% increase in hardness and 40–50% increase in tensile strength were observed in the as-cast composites as compared to aluminium alloy. Uniform distribution of reinforcements and hardness distribution on the entire cross-section clearly reveals that stir casting is an effective method for manufacturing aluminium composites.